The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17082917
|View full text |Cite
|
Sign up to set email alerts
|

Research on Energy Management of Hybrid Unmanned Aerial Vehicles to Improve Energy-Saving and Emission Reduction Performance

Abstract: The rapid development of industry results in large energy consumption and a negative impact on the environment. Pollution of the environment caused by conventional energy sources such as petrol leads to increased demand for propulsion systems with higher efficiency and capable of energy-saving and emission reduction. The usage of hybrid technology is expected to improve energy conversion efficiency, reduce energy consumption and environmental pollution. In this paper, the simulation platform for the hybrid unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…This will encourage landowners to invest in this technology, seeing the long-term investment/return value. In recent years, there have been technical advances on prolonging the airtime of UAVs using solar power [195], hybrid fuel cell systems [196], and petrol-electric hybrid systems [197]. Such developments can have potential applicability in the field of UAVsSS.…”
Section: Development Of Unmanned Aerial Vehicle (Uav) and Robotics Technologiesmentioning
confidence: 99%
“…This will encourage landowners to invest in this technology, seeing the long-term investment/return value. In recent years, there have been technical advances on prolonging the airtime of UAVs using solar power [195], hybrid fuel cell systems [196], and petrol-electric hybrid systems [197]. Such developments can have potential applicability in the field of UAVsSS.…”
Section: Development Of Unmanned Aerial Vehicle (Uav) and Robotics Technologiesmentioning
confidence: 99%
“…In the application of UAV, most of the EMS are aimed at energy saving and emission reduction [21][22][23], including some research on the exploiting of solar energy [23], which is a very green and promising research field. However, as the current technology is not mature enough and extremely dependent on the natural conditions, it cannot be widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Q‐learning method is used in Ref. 44 and showed that the hybrid system can decrease pollutants.…”
Section: Introductionmentioning
confidence: 99%